Nutritional Potential and Antioxidant Activity of Dioscorea spp. Tubers from Mtwara Rural District, Tanzania - Mwanjala, Tumsifu S.; Washa, Washa B.; Nnungu, Stephen I. (Tanzania Journal of Science, 2024)
The wild yam Dioscorea hirtiflora subsp. orientalis, native to the Mtwara rural district in Tanzania, remains underutilized despite its considerable nutritional and health benefits. This study aimed to assess the nutritional composition and antioxidant properties of its tubers. Standard AOAC procedures were employed to analyze dried tuber samples, while antioxidants and antioxidant capacity were evaluated. The tuber was found to have carbohydrates content ranging from 21.02% to 23.57%, crude protein from 1.0% to 1.5%, crude lipids between 0.46% and 0.68%, and crude fiber from 11.26% to 13.52%, with an energy value of 97.26 to 101.1 Kcal/100 g. Vitamin C content varied from 18.9 to 26.4 mg/100 g, beta-carotene from 4.15 to 17.8 µg/g, and lycopene from 6.89 to 9.10 µg/g. Methanol extracts revealed total phenolic content ranging from 60.28 to 122.51 mg GAE/g and flavonoids ranging from 599 to 1240.4 mg RUE/g, with notable DPPH radical scavenging activity, demonstrated an EC50 of 0.04 mg/mL for brown tuber extract and 0.09 mg/mL for white tuber extract. These findings suggest that D. hirtiflora is a rich source of vital nutrients and antioxidants, with potential to enhance local diets and serve as a basis for developing antioxidant-rich supplements or functional foods. Future research should focus on refining extraction techniques and exploring the health applications of this valuable tuber.